2010
DOI: 10.1002/jmr.1001
|View full text |Cite
|
Sign up to set email alerts
|

A new human catalytic antibody Se‐scFv‐2D8 and its selenium‐containing single domains with high GPX activity

Abstract: Glutathione peroxidase (GPX) is a well-known antioxidant selenoenzyme, which can catalyze the reduction of a variety of hydroperoxides and consequently protect cells and other biological tissues against oxidative damage. Many attempts have been made to mimic its function, and a human catalytic antibody Se-scFv-B3 with GPX activity has been prepared in our previous study. This time, a new clone 2D8 that bound specifically to the glutathione analog GSH-S-DNPBu was selected again by using the technology of phage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 46 publications
(56 reference statements)
0
3
0
Order By: Relevance
“…Typical host systems include cyclodextrins, catalytic antibodies, and natural enzymes [6][7][8]. Cyclodextrins (CDs) are well known, naturally-occurring, cyclic oligosaccharides composed of at least six α-1-4-linked α-D-glucopyranoside units.…”
Section: Introductionmentioning
confidence: 99%
“…Typical host systems include cyclodextrins, catalytic antibodies, and natural enzymes [6][7][8]. Cyclodextrins (CDs) are well known, naturally-occurring, cyclic oligosaccharides composed of at least six α-1-4-linked α-D-glucopyranoside units.…”
Section: Introductionmentioning
confidence: 99%
“…Glutathione S ‐transferase (GST) and glutaredoxin (Grx) are natural protein scaffolds with intrinsic GSH‐binding sites and widely used to redesign GPx mimics . Furthermore, a number of GPx mimics have been built by a monoclonal antibody and bioimprinting techniques, which introduce the GSH binding site into the models .…”
Section: Introductionmentioning
confidence: 99%
“…And the fact that the mechanism of Sec incorporation differs from prokaryotes to eukaryotes makes it difficult to directly heterologously express recombinant mammalian selenoproteins in E. coli (8). It has been reported that several GPX mimics with high activity are produced by eukaryotic expression system and chemical method (9)(10)(11)(12)(13). However, the restrictions, such as low yield and short of specificity, make it inappropriate to produce quantities of selenoproteins and predict the structure of the protein scaffold introduced Sec for imitating GPX.…”
Section: Introductionmentioning
confidence: 99%